Efektifitas Dan Kontribusi Pajak Hiburan Terhadap Penerimaan Pendapatan Asli Daerah Kabupaten Lamongan Th.2017-2020 - Amanatul Khoiriyyah; Umar Yeni Suyanto; Rohmatul Fitriyah Dewi (JEMAP, 2022)
The purpose of this study was to determine the effectiveness and contribution of Entertainment Tax revenue to Lamongan Regency's Original Regional Revenue in 2017-2020. Data collection technique used was documentation and data analysis techniques used were descriptive data analysis, effectiveness analysis, and contribution analysis. The results of the study showed that the realization of the entertainment tax on Lamongan Regency's Regional Original Income in 2017-2020 was very effective according to the standards that has been set, showing the average annual effectiveness of 111%.  With the highest level of effectiveness of Entertainment Tax receipts in 2017 which was 229%. The lowest level of entertainment tax revenue effectiveness in 2020, which was 43%. The contribution of entertainment tax to Lamongan Regency's Regional Original Income in 2017-2020 was very less in accordance with the standards that have been set, showing the average annual contribution of 2%. with the highest level of Entertainment Tax Contribution in 2017 at 4% and the lowest Entertainment Tax contribution in 2020 at 1%. In the future, the Lamongan BAPENDA office should have good relations between taxpayers, and provide stricter sanctions to taxpayers who violate